Turnover in information systems development projects - Managing forgetting - Tham, Z.-C.G. (2013)
PACIS 2008 - 12th Pacific Asia Conference on Information Systems: Leveraging ICT for Resilient Organizations and Sustainable Growth in the Asia Pacific Region